A study on the Information needs and behaviour of alternative media journalist in Metro Manila - Cariaga, Danielle Sydney G.; Buenrostro-Cabbab, Iyra S.
This study sought to determine the information needs and seeking behavior of selected alternative media journalists based in Metro Manila. Throughout history, alternative media journalism has made an impact through their critical content and effort to call for social change. Their content, audience, advocacy and experiences distinguish them from mainstream media. The respondents were from Bulatlat (online), Kodao Productions (broadcast and radio), and Pinoy weekly (print). To identify the various motivations and influences that shaped their information needs and behaviour, semi-structured interviews were done via online means such as Zoom through video and audio call, and Facebook through chat and audio call. The journalists’ responses were analyzed and presented using the strands based on Bandura’s Social Cognitive Theory, Blumler and Katz’s User Gratification Theory, and Niedzwiedzka’s Model of information Behaviour. These strands are use, context, and gratification. Results showed that their information needs and motivations usually come from personal influences (advocacy, beliefs, ethics) and environmental influences (political situation, challenges experienced) they encounter. Despite the issues faced by alternative media as they seek, use and share information, they continuously envinsion a better future and drive for the journalists – the content they provide, the audience they serve, and their own brand of journalism. After exploring the information needs and behaviour of journalists, this study came up with recommendations on how media libraries and librarians can use their knowledge and expertise to help them.
Thesis
Keywords: Journalists -- Information needs -- Philippines -- Metro Manila; Information behavior -- Philippines -- Metro Manila; Alternative mass media -- Philippines -- Metro Manila